Employability on vocational high school students in the ”3T” area Bawean Island - Tentama, Fatwa; Santosa, Budi; Ali, Raden Muhammad (Intelektual Pustaka Media Utama, 2024)
Vocational high schools in ”3T” area on Bawean Island have limitations in human resources quality, equipment, production or practice tools, and industrial partnership, which differed from the vocational high schools located in advanced and developed areas. This research objective is to discover the description of employability to the vocational high school students in ”3T” area in Bawean island. The research method applied was the qualitative method using the phenomenology approach. The data collection was obtained through semi-structured interviews. This research participant was eight students at vocational high school